2006
DOI: 10.1603/0046-225x-35.4.1069
|View full text |Cite
|
Sign up to set email alerts
|

Uv-blocking Plastic Films and Nets Influence Vectors and Virus Transmission on Greenhouse Tomatoes in the Humid Tropics

Abstract: We studied the effect of UV-blocked greenhouses made from netting and plastics on the movement and pest status of three important pest of tomatoes: whiteßy (Bemisia tabaci), thrips (Ceratothripoides claratris), and aphid (Aphis gossypii). Under UV-blocked greenhouses, fewer whiteßies, aphids, and thrips entered the greenhouse compared with the ones having more UV intensity. Similarly, signiÞcantly fewer alate aphids and adult B. tabaci/leaf were counted in greenhouses with low UV intensity. Although thrips wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 51 publications
(77 reference statements)
7
50
0
1
Order By: Relevance
“…In the investigations on the use of mulch for protection of plants from virus diseases, three features were often stated: (1) The higher the percentage of soil covered with mulch the higher the efficiency (e.g., Adlerz and Everett 1968;Lehmhus 2001); (2) The efficiency of the mulch decreases over the growing season along with the increasing canopy of the plant (e.g., Brust 2000); (3) The comparably high costs of mulching are only economically justified in high value crops or when severe losses occur regularly due to virus diseases (e.g., Brust 2000). Finally, there is a recent report on the use of UV absorbing fabric (netting and plastics) in greenhouses for aphid control (Kumar and Poehling 2006). Under UV-blocked conditions, fewer aphids (Aphis gossypii Glover) entered the greenhouse compared with the ones having higher UV intensity.…”
Section: Agricultural Implications: Optimisation Of Aphid Monitoring mentioning
confidence: 99%
“…In the investigations on the use of mulch for protection of plants from virus diseases, three features were often stated: (1) The higher the percentage of soil covered with mulch the higher the efficiency (e.g., Adlerz and Everett 1968;Lehmhus 2001); (2) The efficiency of the mulch decreases over the growing season along with the increasing canopy of the plant (e.g., Brust 2000); (3) The comparably high costs of mulching are only economically justified in high value crops or when severe losses occur regularly due to virus diseases (e.g., Brust 2000). Finally, there is a recent report on the use of UV absorbing fabric (netting and plastics) in greenhouses for aphid control (Kumar and Poehling 2006). Under UV-blocked conditions, fewer aphids (Aphis gossypii Glover) entered the greenhouse compared with the ones having higher UV intensity.…”
Section: Agricultural Implications: Optimisation Of Aphid Monitoring mentioning
confidence: 99%
“…Bionet ® provided a signi fi cant greater protection from white fl ies, B. tabaci , than standard net of the same density (Antignus et al 1998 ) . Kumar and Poehling ( 2006 ) reported that covering greenhouses with UV-blocking plastic and Bionet ® signi fi cantly reduced both attraction and invasion of white fl ies ( B. tabaci ), aphids ( A. gossypii ) and thrips ( Ceratothripoides claratus ), compared to UV-transmitting materials. Growing lettuce under UV-blocking materials decreased aphid density and the spread of aphid-transmitted viruses (Legarrea et al 2012 ) .…”
Section: Above the Plantmentioning
confidence: 99%
“…The first report on the effects of UV-blocking plastic films was (Nakagaki et al 1982), but the emphasis on modifying the characteristics of plastics for agriculture is a recent development (see review, Diaz and Fereres 2007). The effects of UV-absorbing films and nets on reducing the populations of different species of insect pests (aphids, leafhoppers, thrips, and whiteflies) have been well documented (Antignus et al 1996;Costa and Robb 1999;Costa et al 2002;Chyzik et al 2003;Kumar and Poehling 2006;Doukas and Payne 2007b;Weintraub et al 2008). Furthermore, these UV-absorbing materials have proven to be very effective in reducing the spread of insect-transmitted plant viruses (Antignus et al 1996;Diaz et al 2006).…”
Section: Insect Exclusion Screensmentioning
confidence: 99%